P102 The impact of a dedicated interventional team in the management and outcome of central airways obstruction in lung cancer patients. (11th November 2022) - Zaki, I; Arooj, P; Crowle, D; Talbot, A; Nicholson, TW; Marchbank, A; Telisinghe, LA; Daneshvar, C
Abstract : Introduction: The approach to central airways obstruction in lung cancer varies. Having previously established benchmarking in disease prevalence, management and outcomes in 2014, we re-audited our local approach following the introduction of a dedicated interventional service. Method: New lung cancer diagnoses in 2019 were assessed for evidence of central airways disease. Comparisons were made with our previous audit from 2014. Simple descriptive statistics were used. To identify factors associated with death, all data were combined (2014/2015 and 2019/2020). Logistic regression was used to determine the effect of age, gender, tumour type and degree of obstruction to identify independent factors associated with 60-day mortality. Results: No differences were seen in the clinical characteristics of people with CAO presenting in 2014/2015 and 2019. Deaths were high, with 45% of people dying within 90 days of a diagnostic CT. There was no difference in the proportion dying in 2014/2015 and 2019. Over the two time periods the proportion with CAO<50% increased (12/30 [40%] in 2014/2015 versus 18/30 [60%] in 2020; p=0.07). The proportion of people eligible for intervention and receiving intervention was unchanged between 2014/2015 and 2019 (5/16 [31%] in 2014/2015 and 3/9 [33%] in 2019). However the time to intervention improved (60.5 [interquartile range IQR 29.5–120.0] days in 2014/2015 and 7.0 [IQR 6.0–7.0] days in 2019; p=0.03). Although limited by the number of outcomes, after adjusting for age, gender and degree of obstruction, the odds of death was lower among people with squamous cell carcinoma compared to those with other tumour types (squamous cell cancers 8/36 [22%] vs small cell lung cancer 5/21 [24%] versus other cancers 30/74 [40%]; adjusted odds ratio [aOR] 0.40 [95%CI 0.16–1.02], aOR 0.46 [0.15–1.40]; p=0.09). Conclusions: The impact of the interventional service did not lead to an increase in intervention, however the time to procedure improved significantly. Understanding decision making and identifying those that benefit the greatest from intervention needs further work.